Pengaruh Tingkat Pendidikan dan Motivasi Orang Tua Terhadap Minat Belajar Siswa Kelas Atas SDN 03 Buran Tahun 2015/2016 - Sari, Aprilia Dwi Puspita (2016)
The purpose of this research was to determine (1) The effect of parents' educational level of student interest of high class in SDN 03 Buran Year 2015/2016, (2) Influence of parents' motivation of student interest of high class in SDN 03 Buran Year 2015/2016, (3) The effect of parents' educational level and motivation of student interest of high class in SDN 03 Buran Year 2015/2016. This research is quantitative research with survey research design. Based on the analysis of multiple linear regression equation Y = 56.010 + 0,133X1 + 0,285X2. The results of the data analysis significance level of 5% was obtained: (1) The effect of parents' educational level of the learning interest. This is based on test results t is known that tcount> ttable, namely 2.859> 2.011 and the significance value <0.05 is 0.006 with the relative contribution (SR) of 0.59% and the effective contribution (SE) of 0.21%. (2) Parents' motivation effect of the learning interest. This is based on the test results t is known that tcount> ttable, namely 2.179> 2.011 and the significance value <0.05 is 0.034 with the relative contribution (SR) of 0.41% and the effective contribution (SE) of 0.14%. (3) The effect of parents' educational level and motivation of the learning interest. This is based on the test F known that Fcount> Ftable, namely 12.708> 3.20 and a significance value <0.05 is 0.000. It can be concluded that the parents' educational level greater influence on student interest of high class in SDN 03 Buran Year 2015/2016. Keyword: Educational level, Parents' motivation, Learning interest